Sld7, an Sld3-associated protein required for efficient chromosomal DNA replication in budding yeast - Tanaka, Tamon (Nature Publishing Group, 2011)
Genetic screening of yeast for sld (synthetic lethality with dpb11) mutations has identified replication proteins, including Sld2, -3, and -5, and clarified the molecular mechanisms underlying eukaryotic chromosomal DNA replication. Here, we report a new replication protein, Sld7, identified by rescreening of sld mutations. Throughout the cell cycle, Sld7 forms a complex with Sld3, which associates with replication origins in a complex with Cdc45, binds to Dpb11 when phosphorylated by cyclin-dependent kinase, and dissociates from origins once DNA replication starts. However, Sld7 does not move with the replication fork. Sld7 binds to the nonessential N-terminal portion of Sld3 and reduces its affinity for Cdc45, a component of the replication fork. Although Sld7 is not essential for cell growth, its absence reduces the level of cellular Sld3, delays the dissociation from origins of GINS, a component of the replication fork, and slows S-phase progression. These results suggest that Sld7 is required for the proper function of Sld3 at the initiation of DNA replication.